Demographic Development in the Northeastern Slovenia - Horvat, Uroš; Davidović, Danijel (Podeželje, 2026)
The paper presents the demographic development in Northeastern Slovenia at the settlement level in the period from 1869 to 2025. The analysis is based on census data, combined with the physical-geographical and functional spatial division and typology of settlements. The results reveal pronounced spatial differentiation of demographic development in different time periods. The most distinctive pattern is the polarization between lowland areas with early demographic minimum and later growth, and upland areas, where most settlements reached their demographic maximum before or shortly after the Second World War, and then entered a long-term process of depopulation. In the most recent period, spatial patterns are less related to relief and reflect the increasing importance of migration processes and functional connections, associated with suburbanization in the hinterland of larger urban centers. In recent times, this has been spreading from the plains to the hilly hinterland of Maribor, Ptuj, Lenart and Slovenska Bistrica, but not in the vicinity of Murska Sobota. The findings are consistent with short-term demographic projections, which predict a pronounced aging of the population and other unfavorable demographic trends, especially in the Pomurje statistical region.